Efektivitas Penggunaan Google Classroom dalam Proses Pembelajaran Dasar Listrik dan Elektronika - Danny Afredo; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research is motivated by the current situation. Where at this time the world is being hit by an outbreak of the COVID-19 disease which has resulted in activities / learning processes being carried out online for all levels of education. During the development of education in the 4.0 revolution era, it required the entire community, especially teachers and students, to take advantage of the development of digital technology in the learning process. This study aims to determine the effectiveness of Google Classroom in improving student learning outcomes in Basic Electrical Electronics subjects at SMK 1 Padang. This research uses a descriptive method. The subjects in this study were class X DLE subject teachers, and class X TITL students at SMK 1 Padang. Based on the results of the study, the results of the media validation were in a valid category, and material validation was in a valid category. The validators considered that learning using Google Classroom was valid. Due to time constraints, the research on the effectiveness of using google classroom which consists of 6 basic competencies only focuses on one basic competency, namely basic competence, namely KD 3.9 Applying electric current and voltage. the practicality test by the class X TITL students stated that this research was in the very practical category. The effectiveness test states that this research is in the effective category. So it can be concluded that the use of Google classroom can be applied in the online teaching and learning process, especially in Basic Electrical Electronics subjects and can affect student learning outcomes.